PENGARUH BUDAYA SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA DAN IMPLIKASINYA TERHADAP HASIL BELAJAR SISWA (Survey Pada Siswa Madrasah Tsanawiyah Swasta di Kota Banjar) - RITA PATONAH (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2018)
The research is aimed to convey the influence of school culture towards student’s learning motivation and it’s implication on student’s learning achievement (the survey on students of MTs in Banjar). The main case discussed in this research is how far the direct effect of the four independent variables towards the increasing student’s learning achievement and indirect effect through variable of student’s learning motivation. The object of the research consists of four independent variables, they are: social cultur (X1), academic culture (X2), quality culture (X3) and artifac (X4), one intervening variable that is  student’s learning motivation (X5) and one dependent variable that is student’s learning achievement (Y). Meanwhile, the subjects of the research are the students of MTs in Banjar about 133 students. Random sampling and path analysis are used in the research. Based on the statistics experiment is showed that social culture influenced student’s learning motivation about 15,13%. Academic culture influenced student’s learning motivation about 20,79%. Quality culture influenced student’s learning motivation about 3,03%. Artifac influencedd student’s learning motivation about 0,98%. Whereas the simultant influenced among social culture, academic culture, quality culture, artifac towards student’s learning motivation about 61,9%. Social culture influenced student’s learning achievement about 0,03%. Academic culture influenced student’s learning achievement about 1,96%. Quality culture influenced student’s learning achievement about 2,10%. Artifac influenced student’s learning achievement about 6,50%. Student’s learning motivation influenced student’s learning achievement about 60,53%. Whereas the simultant influenced among social culture, academic culture, quality culture, artifac and  student’s learning motivation towards student’s learning achievement about 77,6%.Kata Kunci: social culture, academic culture, quality culture, artifac, student’s learning motivation, student’s learning achievement